ANALISIS EFEKTIFITAS IMPLEMENTASI KEBIJAKAN PEMERINTAH DALAM KONTEKS KETERLIBATAN PEMANGKU KEPENTINGAN (STAKEHOLDER ENGAGEMENT): STUDI KASUS PROGRAM REVALUASI BARANG MILIK NEGARA PADA KEMENTERIAN KEUANGAN - Eko Prasetyo (JURNAL ILMIAH ILMU ADMINISTRASI, 2020)
Policy implementation in the government programs and activities is often constrained by weak coordination of stakeholders. The State-Owned Property (SOP) Revaluation Program conducted by the Ministry of Finance in 2017 and 2018 runs slowly and takes a long time to validate the revaluation data. This study intends to uncover the causes of these constraints and how to increase stakeholder engagement in the SOP Revaluation Program. The research method used is qualitative research. The research will conduct literature studies based on various references, documents, and reliable sources at the Directorate General State Asset Management of the Ministry of Finance. This research shows that the policy implementation in the SOP Revaluation Program has not been effective. This shows the low-level of stakeholder engagement caused by the low capability of the human resources at the units of the Ministries/Institutions, the low quality of the SOP management by the units, and the low commitment of the units to achieve the objectives of the program. For this reason, stakeholder mapping needs to be done, as well as choosing a different approach for different stakeholders.